PENGARUH TUTUPAN VEGETASI TERHADAP EROSI PADA HULU SUNGAI BATANG ARAU, KOTA PADANG - Silta Yulan Nifen; Idris Idris (Ensiklopedia of Journal, 2021)
The Batang Arau River is one of the major rain catchment areas in the city of Padang. However, there are various problems including erosion problems. The aim of this research is to predict the rate of erosion that occurs in the Upper Batang Arau River Catchment using the MUSLE method. MUSLE method uses Arc.Gis 10.3 software and NDVI 4.5 software to calculate vegetation density. The results showed that the estimated land surface erosion that occurred in the Upper Batang Arau River Catchment Area was 14.12 cm / year or 254.16 tons / ha / year. The amount of erosion that occurs in the Upper Batang Arau River Catchment Area is valued at 254.16 tons / ha / year, so it is classified as a heavy category because the erosion value ranges from 180